Model Ketahanan Pangan Berperspektif Gender - Poerwanto Poerwanto; Muhamad Supraja (DIMENSI - Journal of Sociology, 2016)
This study was conducted to determine the role of women in household food security, identify alternatif of local food resources (non-rice) adaptive to the role of women and their utilization, and women’s empowerment modelingbasedpotential of local food resources. The method used is qualitative and quantitative. The respondents of this study is a housewifes who lives in the three typhologies of village, i.e. village of paddy fields, dry village, and beach village. The results show that women have a considerable role in household food security, both from the aspect of food production, procurement / preparation of food, food processing, and food quality. Several types of local food that is found i.e. cassava, bananas, maize, sweet potato, canna, taro, arrowroot, Uwi, gembili, breadfruit, juwawut, and kimpul (for food crops); cassava leaves, papaya leaves, leaf melinjo, spinach, mustard greens, cabbage, beans, and spinach (forvegetables); as well as mango, papaya, banana, melon, jackfruit and rambutan (for fruits). Alternative crops (non-rice) can be processed into some kind of processed food. Cassava, maize and bananas is a commodity that most processed into some kind of processed food product variants.Although it looks fairly prominent role of women in various aspects of household food security, but many found the weaknesses and the potential that can be optimized in order to improve their food security.Therefore, it takes several empowerment programs implemented to support the optimization of their role, among others, increasing knowledge about food consumption that meets the criteria B2SA, habituationfor consumption local food in compliance with food daily, developing culinary industry based on local food, and the optimization of land use.